MEDIA TELEVISI, PEMERTAHANAN DAN PERENCANAAN BAHASA INDONESIA - I Komang Sulatra (SPHOTA: Jurnal Linguistik dan Sastra, 2014)
ABSTRACT Language is a dynamic entity. As a dynamic entity, language echangeisone of the characteristics of a language. The change can be positive or conversely to the negative side. As a national language, Bahasa is intended to be developed into one of international languages, but in some cases the condition is far from the target. It happened because the speakers attitude toward the standard language remain unstable. This condition can be seen in the use of bahasa in mass media, especially the use of bahasa in Television program. The domination of non standard form has given bad effect to the standard language, such as the quality and the quantity of the standard language’s domain become lessen. Due to those problems, good coordination between the government, society, and mass media are required in developing Indonesian through language planning. Key words: language maintenanace, language planning, mass media, televisión and entertainment program